Geniposide Possesses the Protective Effect on Myocardial Injury by Inhibiting Oxidative Stress and Ferroptosis via Activation of the Grsf1/GPx4 Axis - Shen, Yuehong; Wang, Xindong; Shen, Xinyu; Wang, Yue; Wang, Shulin; Zhang, Yunyun; Yao, Xiaoming; Xu, Yijiao; Sang, Ming; Pan, Jiamin; Qin, Yu; Zhou, Qian; et al. (Frontiers in Pharmacology, 2022)
Reactive oxygen species (ROS) produced in the area of myocardial ischemia can induce cardiomyocyte injury and death, resulting in cardiac remodeling. Ferroptosis, known as an iron-dependent oxidative stress-related cell death, that reportedly is an essential death mechanism in cardiomyocytes. However, it is unclear whether oxidative stress products can further induce ferroptosis and aggravate cardiomyocyte injury. Geniposide (GEN), a major active component of Gardenia jasminoides, has natural antioxidant activity and cardioprotective effect. Herein, we evaluated the role of ferroptosis in myocardial injury and protective effect of GEN on myocardial ferroptosis. We first detected iron overload, massive ROS, and lipid peroxidation, which were characteristics of ferroptosis in ferric ammonium citrate (FAC)-treated cardiomyocytes. The iron overload-induced oxidative stress and ferroptosis aggravated cardiomyocyte injury, and these effects were countered by GEN treatment. Further, we found the similar phenotypic changes and decreased mitochondrial function in hydrogen peroxide (H2O2)-induced cells. Additional treatment of GEN significantly reversed these changes. Interestingly, RNA-binding protein Grsf1, which directly upregulates Gpx4 expression at the translational level, was activated by GEN in myocardial oxidative injury. The specific knockdown of Grsf1 increased their sensitivity to ferroptosis and weakened the cardioprotection of GEN in H2O2-treated cardiomyocytes. In vivo, treatment with GEN reduced iron overload and accumulation of lipid peroxides, thereby protecting the heart from ischemic damage. Collectively, our study revealed the pathogenesis of oxidative stress and ferroptosis associated with myocardial ischemia, and indicated that GEN shows antioxidant and anti-ferroptosis effects by activating the Grsf1/Gpx4 axis and thus may be a potential therapeutic target for myocardial injury.